Impaired turnover of hyperfused mitochondria in severe axonal neuropathy due to a novel DRP1 mutation. (7th September 2019) - Longo, Fabiana; Benedetti, Sara; Zambon, Alberto A; Sora, Maria Grazia Natali; Di Resta, Chiara; De Ritis, Daniele; Quattrini, Angelo; Maltecca, Francesca; Ferrari, Maurizio; Previtali, Stefano Carlo
Abstract: Mitochondria undergo continuous cycles of fusion and fission in response to physiopathological stimuli. The key player in mitochondrial fission is dynamin-related protein 1 (DRP1), a cytosolic protein encoded by dynamin 1-like ( DNM1L ) gene, which relocalizes to the outer mitochondrial membrane, where it assembles, oligomerizes and drives mitochondrial division upon guanosine-5′-triphosphate (GTP) hydrolysis. Few DRP1 mutations have been described so far, with patients showing complex and variable phenotype ranging from early death to encephalopathy and/or optic atrophy. The disease is the consequence of defective mitochondrial fission due to faulty DRP1 function. However, the underlying molecular mechanisms and the functional consequences at mitochondrial and cellular level remain elusive. Here we report on a 5-year-old girl presenting psychomotor developmental delay, global hypotonia and severe ataxia due to axonal sensory neuropathy harboring a novel de novo heterozygous missense mutation in the GTPase domain of DRP1 (NM_012062.3:c.436G>A, NP_036192.2: p.D146N variant in DNM1L ). Patient's fibroblasts show hyperfused/balloon-like giant mitochondria, highlighting the importance of D146 residue for DRP1 function. This dramatic mitochondrial rearrangement phenocopies what observed overexpressing DRP1-K38A, a well-known experimental dominant negative version of DRP1. In addition, we demonstrated that p.D146N mutation has great impact on peroxisomal shape and function. The p.D146N mutation compromises the GTPase activity without perturbing DRP1 recruitment or assembly, causing decreased mitochondrial and peroxisomal turnover. In conclusion, our findings highlight the importance of sensory neuropathy in the clinical spectrum of DRP1 variants and, for the first time, the impact of DRP1 mutations on mitochondrial turnover and peroxisomal functionality.